Metabolic syndrome risk factors in overweight, obese, and extremely obese brazilian adolescents - Rizzo, Anapaula C.B. [UNESP]; Goldberg, Tamara Beres Lederer [UNESP]; Silva, Carla C.; Kurokawa, Cilmery Suemi [UNESP]; Nunes, Helio R.C. [UNESP]; Corrente, José Eduardo [UNESP] (Springer Nature, 2013)
Background: Obesity in infancy and adolescence has acquired epidemic dimensions worldwide and is considered a risk factor for a number of disorders that can manifest at an early age, such as Metabolic Syndrome (MS). In this study, we evaluated overweight, obese, and extremely obese adolescents for the presence of MS, and studied the prevalence of single factors of the syndrome in this population. Methods. A total of 321 adolescents (174 females and 147 males) aged 10 to 16 years, attending the Adolescent Outpatient Clinic of Botucatu School of Medicine, Brazil, between April 2009 and April 2011 were enrolled in this study. Adolescents underwent anthropometric evaluation (weight, height, and abdominal circumference) and Body Mass Index (BMI) was estimated according to age and gender, following Disease Control and Prevention Centers recommendations (CDC, 2000). Blood pressure was measured and individuals with BMI ≥ 85§ssup§th§esup§ percentile were submitted to laboratory evaluation for Total Cholesterol, HDL and LDL Cholesterol, Triglycerides, Fasting Insulinemia, and Fasting Glycemia to identify MS factors, according to the criteria suggested by the International Diabetes Federation. Insulin resistance was calculated by HOMA-IR, Quicki, and Fasting Glycemia/Fasting Insulinemia (FGI). Results and discussion. Of the 321 adolescents, 95 (29.6%) were overweight, 129 (40.2%) were obese, and 97 (30.2%) were extremely obese. Around 18% were diagnosed with MS. The most prevalent risk factors were abdominal circumference ≥90§ssup§th§esup§ percentile (55%), HDL < 40 mg/dL (35.5%), High Pressure ≥130/85 mm/Hg (21%), Triglycerides ≥150 mg/dL (18.5%), and Fasting Glycemia ≥100 mg/dL (2%). Insulin resistance was observed in 65% of the adolescents. Conclusion: An increased prevalence of overweight and obesity, together with cardiometabolic risk factors such as dyslipidemia and abnormal blood pressure, were observed in adolescents, contributing to the onset of metabolic syndrome at younger ages. Risk factors for MS were more prevalent in females. © 2013 Rizzo et al.; licensee BioMed Central Ltd.
Keywords: Adolescents; Insulin resistance; Metabolic Syndrome; Obesity; Risk factors; high density lipoprotein cholesterol; low density lipoprotein cholesterol; triacylglycerol; adolescent; blood pressure measurement; body height; body mass; body weight; child; cholesterol blood level; diet restriction; female; glucose blood level; human; insulin resistance; insulinemia; major clinical study; male; metabolic syndrome X; obesity; public health service; risk factor; school child; waist circumference; Adolescent; Blood Glucose; Blood Pressure; Body Composition; Body Mass Index; Body Weight; Brazil; Child; Cholesterol; Fasting; Female; Humans; Insulin Resistance; Male; Metabolic Syndrome X; Nutrition Assessment; Overweight; Prevalence; Risk Factors; Triglycerides